Kontaminasi Gas CO di Terminal Jombor Yogyakarta: Indonesia - Mudhofar, Moh Ade; Nugroho, Adam Rus; Wantoputri, Noviani Ima (Jurnal Sains & Teknologi Lingkungan, 2026)
The risk of air pollution originating from the transportation sector constitutes a primary concern in this study. Terminal Jombor Yogyakarta, a Type B public transportation terminal with high vehicular activity serving Intercity–Interprovincial (AKAP), Intercity–Intraprovinical (AKDP), and Trans Jogja routes, has the potential to contribute significantly to ambient air pollution due to vehicle emissions. This study focuses on identifying carbon monoxide (CO) concentrations and analyzing the spatial distribution of CO levels within the Terminal Jombor area. A quantitative approach was employed through direct observation and measurements at three monitoring points. The results indicate that the highest CO concentration was recorded at Point 1 on the third day of observation (weekday), reaching 10,883.2 µg/Nm³, exceeding the ambient air quality standard of 10,000 µg/Nm³. Meanwhile, the highest average CO concentration was observed at Point 3, with a value of 2,446 µg/Nm³. This point is located near the terminal exit area, where vehicles tend to idle before accelerating, thereby increasing CO emissions. Furthermore, CO concentrations on weekdays were found to be higher than those recorded on weekends. Spatial distribution analysis revealed that Points 2 and 3 fall into the moderate to high concentration categories. These findings indicate the need for intervention by relevant authorities to mitigate potential health impacts associated with carbon monoxide exposure in the Terminal Jombor area.